Blue straggler populations beyond the Milky Way - Richard de Grijs; Weijia Sun; Chengyuan Li; Licai Deng
Although the formation of blue straggler stars (BSSs) is routinely attributed to stellar interactions in binary systems, the relative im- portance of the direct collision and slow(er) stellar coalescence formation channels is still poorly understood. We selected a sample of 24 Magellanic Cloud star clusters for which multi-passband Hubble Space Telescope images are available to address this outstanding question. We compiled a BSS database, containing both traditional and evolved BSSs. We found a robust correlation between the number of BSSs in a cluster's core and its core mass, NBSS;core / M0:510±07 core , which supports the notion that BSS formation is linked to a population's binary fraction. At low stellar collision rates, the mass-normalised number of BSSs does not appear to depend on the collision rate, which implies that the coalescence-driven BSS formation channel dominates. Com- parison with simulations suggests that stellar collisions contribute less than 20% to the total number of BSSs formed.
Keywords: Astronomy